Child Rape Cases in News Text: Sara Mills’ Critical Discourse Analysis - Azzahra, Syifa Shafira; Riyanto, Edi Dwi; Afdholy, Nadya; Salsabila, Nur Shafa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Sexual violence against children has become a world problem that can occur anytime, anywhere, and be carried out by anyone, and the number of cases is increasing continuously. This phenomenon is a critical problem because child victims who are still in the phase of adolescence can be at risk of disrupting the child's growth and development process and changing the child's behavior. This study aims to analyze news articles on child rape cases in the online media portal Liputan6.com and Merdeka.com using the Critical Discourse Analysis approach, specifically the Sara Mills model. This study employs qualitative research with a descriptive qualitative approach. The data utilized consists of news articles on child rape published on the online news portals Liputan6.com and Merdeka.com. The Critical Discourse Analysis by Sara Mills is employed to comprehend the language construction and ideologies of these articles. The findings of this study are that the subject-object position in the two news discourses reveals that girls are positioned as objects and journalists and third person as subjects. Then, the Writer-Reader Position in Liputan6.com's news discourse reveals that the writer is the subject and the reader is positioned as the reader acts as the perpetrator, while in the Merdeka.com news discourse, it is revealed that the writer places women as subjects and men as objects. Readers are positioned as women, and the author views the audience as women. In this research, three strategies for presenting victims of sexual harassment were also found, namely character, focalization, and schemata (scheme).